Comparative cooking performance of rice-cassava starch vs. malagkit in ma-chang - Viceral, Zaida Bandoja; Guzman, Matilde P. (1978.)
A study was conducted to determine the acceptability and shelf-life of ma-chang, a Chinese suman, made from a composite of cassava starch (gawgaw) and ordinary rice. This food item was found to be nutritious, containing approximately 123 calories and 5.27 grams protein per 75 grams cooked weight. The product was rated as acceptable as the conventional all-malagkit ma-chang by trained and untrained panelists. Results of subjective and objective evaluations indicated that a 50:50 blend of rice and cassava starch by weight stimulates the desirable qualities of glutinous rice. Tenderness was the most important determining characteristic. The optimum length of storage of ma-chang at ordinary room temperature (29°C, 54% RH) was two days, indicating no significant organoleptic changes.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Glutinous rice; Cassava starch